The Role Of Christian Religious Education In Overcoming Tiktok Addiction In Junior High Schools - Dina Lorensa Br Ginting; Bangun Bangun; Hersakso Sinurat (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
This study aims to examine the influence of Christian Religious Education in overcoming TikTok addiction at SMP Negeri 1 STM HUU. This study used a descriptive quantitative method, with data collection techniques through observation, interviews, and documentation. The subjects were Christian Religious Education teachers and students in grade VII-A who actively used TikTok. The results of this study indicate that Christian Religious Education Plays a role in overcoming TikTok addiction through teaching faith values, character building, and spiritual strengthening. Christian Religious Education teachers provide guidance through Bible teaching and practical advice to help students develop self-control, manage their time, and focus on positive activities. Christian Religious Education plays a crucial role in helping students reduce TikTok addiction by instilling spiritual vaues, fostering discipline, and guiding students toward responsible technology use.